FORMALIDADES PARA LA VALIDEZ JURÍDICA DE LOS TÍTULOS EJECUTIVOS - Villano Cuenca, Mariuxi Alexandra (2016)
For that a legal instrument such as the titles are executives, it is necessary to have an obligation to give or do anything, because if you do not set which is an obligation that must be met there can be no talk of enforceability, so that the title executive must be clear and explicit about the convention of the obligation, to more than that must contain the requirements for a readily apparent obligation on both quality and amount. The title executive is a document that contains the representation of an act, instrument to which the law assigns you precisely the quality to be able to start a process of implementation, it is necessary to do this is take this the meaning of this law and how substantial and formal element: the title in substantial sense is the act that it is the will of the law; that should be formal document in which this act is content. The solemnities are part of the formalities as it relates to the titles, in addition to being a compulsory prerequisite needed to keep the executive titles is perfected, as they are subjects observance of the special formalities, of which would depend on their effectiveness, and its legal validity, therefore, the solemnity is, also, a requirement for validity, and required by law, such as element of which depends on the very existence of trade obligations and mercantile in Ecuador. 5 Enforceable titles for their legal effectiveness, and the validity of the documents, they can be sued the executive express obligations, clear and enforceable that documents that originate from the debtor or of its causative agent, and constitute full proof against him, or those emanating from a judgment of conviction overturned by judge or court in any jurisdiction in the administration of justice, and the other documents that point to the law.